2015
DOI: 10.1016/j.ehb.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Education, gender, and state-level disparities in the health of older Indians: Evidence from biomarker data

Abstract: Using new biomarker data from the 2010 pilot round of the Longitudinal Aging Study in India (LASI), we investigate education, gender, and state-level disparities in health. We find that hemoglobin level, a marker for anemia, is lower for respondents with no schooling (0.7 g/dL less in the adjusted model) compared to those with some formal education and is also lower for females than for males (2.0 g/dL less in the adjusted model). In addition, we find that about one third of respondents in our sample aged 45 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Earlier studies showed cross-state variations were less consistent across different cognitive skills [5]. In this study, the proportion of urban population in each state was not significantly associated with cognitive function; however, the direction of the coefficient suggested that residents of states with a higher proportion of urban population showed better cognition, which is similar to the findings from previous research [5, 32, 46]. A state’s higher proportion of urban population (online suppl.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Earlier studies showed cross-state variations were less consistent across different cognitive skills [5]. In this study, the proportion of urban population in each state was not significantly associated with cognitive function; however, the direction of the coefficient suggested that residents of states with a higher proportion of urban population showed better cognition, which is similar to the findings from previous research [5, 32, 46]. A state’s higher proportion of urban population (online suppl.…”
Section: Discussionsupporting
confidence: 82%
“…Geographic differences in cognitive function in India have been documented in previous literature [5, 32, 46]. Earlier studies showed cross-state variations were less consistent across different cognitive skills [5].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…LASI also measured anthropometric parameters and physical performance, and collected dried blood spot (DBS) specimens using a standardized protocol (Lee et al 2015). The analysis in this paper is restricted to 1,460 respondents who were at least 45 years old.…”
Section: Methodsmentioning
confidence: 99%